2013
DOI: 10.1007/s00701-013-1748-3
|View full text |Cite
|
Sign up to set email alerts
|

Community consultation in emergency neurotrauma research: results from a pre-protocol survey

Abstract: Our community consultation survey shows that the proposed trial is acceptable to the public. In addition, the results suggest high levels of acceptability of surrogate consent by next of kin or independent doctor amongst our community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 18 publications
0
9
0
1
Order By: Relevance
“…A survey conducted as part of community consultation for a trial evaluating a pre-hospital intervention for seizures found that 78 % (n = 1901) of respondents supported the concept of third-party consent, and 65 % indicated willingness to be enrolled with the consent of a family member even if there was no direct benefit to themselves [ 44 ]. A community consultation for a neurosurgical trial found 91 % (n = 171) of participants were accepting of surrogate consent by a doctor independent of the trial [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…A survey conducted as part of community consultation for a trial evaluating a pre-hospital intervention for seizures found that 78 % (n = 1901) of respondents supported the concept of third-party consent, and 65 % indicated willingness to be enrolled with the consent of a family member even if there was no direct benefit to themselves [ 44 ]. A community consultation for a neurosurgical trial found 91 % (n = 171) of participants were accepting of surrogate consent by a doctor independent of the trial [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…While this is a good starting point, we should highlight that each of those studies related to the use of potential treatment that may have had direct benefit to the subject. In fact, the Corticoid Randomization after Significant Head Injury (CRASH) Trial [35] evaluated tranexamic acid in TBI; Clark et al [36] was evaluating the role of decompressive craniectomy for evacuation of an acute subdural haematoma, and Scotton et al [37] was evaluating a subdural evacuating port system as a minimally invasive alternative to burr-hole evacuation. On the contrary, the study outlined in our surveys, although not influencing our standard of care, might not necessary lead to any direct benefit for the participants.…”
Section: Discussionmentioning
confidence: 99%
“…The pilot highlighted the need to promote this and train sites about appropriate use of IHP consent. There is evidence from a public opinion survey on patient inclusion in severe traumatic brain injury (TBI) clinical trials that 91% of respondents would be happy for an independent doctor to assent 48 . Despite this, we have found there is persistent institutional reluctance to use such proxy consent processes, which is only likely to be overcome by continued adoption into trials where appropriate.…”
Section: Discussionmentioning
confidence: 99%